Enhancing Infrastructure Competitiveness in Alignment With COP-29 Climate Goals - Mustafayeva Gulnisa Alisafa; Mammadova Samira Yashar; Balajayeva Tahmina Pasha (BIO Web of Conferences)
Climate change has put more pressure on infrastructure development worldwide, especially in terms of meeting various international commitments such as those dictated by COP-29. In this context, aligning infrastructure projects with climate goals without compromising competitiveness, or in other words, enhancing competitiveness, has become one of the most important challenges for all governments and industries worldwide. It formulates the inclusion of climate resilience and sustainability in infrastructure development while addressing competitiveness based on the COP-29 goals. The main point of the analysis is to identify and analyze the different ways in which infrastructure becomes climate resilient and at the same time contributes to economic growth, maintaining a competitive advantage in the global market. It uses a mixed-methods approach, combining case studies of successful infrastructure projects with a review of the supporting policy framework and technological innovations to support climate-aligned competitiveness. The results of this study show that, in addition to achieving climate goals, infrastructure projects with integrated sustainability practices deliver long- term economic benefits such as cost savings, improved public health, and increased investor confidence. The implication of these findings is that integrating climate considerations at all levels of infrastructure planning and implementation is essential for competitiveness in a world that is rapidly changing both economically and environmentally. It is therefore an essential requirement for environmental sustainability, as well as a strategic opportunity to enhance competitiveness. The article argues that policymakers and industry leaders, in collaboration with other stakeholders, must ensure that infrastructure projects contribute to both climate resilience and economic prosperity through a well-coordinated mechanism.